Upaya Menghentikan Perundungan di Sekolah: Penyuluhan dan Edukasi Anti-Bullying untuk Siswa Sekolah Dasar di Desa Colo Kabupaten Kudus - Aprastuti Puspita Sari; Lafayeth Esha Syahrani; Mutia Agustia Ningsih; Heni Susanti (Universitas Negeri Semarang, 2026)
This community service activity aims to increase the understanding of elementary school students in Colo Village, especially at SD 01 Colo and MI NU Thoriqotus Sa'diyah, about various aspects of bullying. Bullying is an aggressive behavior that can disrupt students' sense of security and comfort at school, and is often carried out without the perpetrators realizing it. This activity emphasized the importance of social and emotional education in bullying prevention efforts, involving all relevant parties, including teachers and parents. The socialization included an introduction to various types of bullying, its negative impacts, and strategies to overcome bullying. With a structured approach and the use of effective media such as PowerPoint, students are expected to recognize, prevent and overcome bullying, so as to create a safer and more supportive school environment.